2021
DOI: 10.1080/21655979.2021.1945361
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA miR-145-5p inhibits Phospholipase D 5 (PLD5) to downregulate cell proliferation and metastasis to mitigate prostate cancer

Abstract: Prostate cancer (PCa), a frequently detected malignant tumor, is the fifth leading global cancer mortality cause in men. Although research has improved the PCa survival rate, significantly reduced survival occurs among patients at the metastatic stage. MiRNAs, which are short noncoding proteins, are crucial for several biological roles, essential for PCa proliferation, differentiation, multiplication, and migration. The investigation aimed to explore miR-145-5p and PLD5 association and clarify their function i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Therefore, we performed a ceRNA analysis using the TCGA data and found that RP11-354B3.1 regulated MAPK4 expression by acting as a ceRNA for miR-145-5p in GC, which was further confirmed by luciferase report assay. miR-145 has been a well-known tumor suppressive microRNA in diverse types of cancer, including prostate cancer (Liu et al, 2021), hepatocellular carcinoma (Wang et al, 2021) and esophageal carcinoma (Fan et al, 2021). Our findings also confirmed that up-regulation of miR-145-5p could inhibit GC cells proliferation and decrease MAPK4 protein expression, which is consistent with the phenotype induced by down-regulation of RP11-354B3.1.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, we performed a ceRNA analysis using the TCGA data and found that RP11-354B3.1 regulated MAPK4 expression by acting as a ceRNA for miR-145-5p in GC, which was further confirmed by luciferase report assay. miR-145 has been a well-known tumor suppressive microRNA in diverse types of cancer, including prostate cancer (Liu et al, 2021), hepatocellular carcinoma (Wang et al, 2021) and esophageal carcinoma (Fan et al, 2021). Our findings also confirmed that up-regulation of miR-145-5p could inhibit GC cells proliferation and decrease MAPK4 protein expression, which is consistent with the phenotype induced by down-regulation of RP11-354B3.1.…”
Section: Discussionsupporting
confidence: 82%
“…MiR-145, an anti-tumor microRNA [ 38 , 39 ], was validated to participate in multiple BC biological behaviors [ 40 , 41 ]. Jiang et al found that miR-145 was a negative correction with HBXIP in BC tissues and it suppressed BC cell proliferation via targeting HBXIP [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs are known for mediating their target genes’ post-transcriptional silencing by targeting the 3ʹ-UTR of corresponding mRNA [ 35 ]. For instance, miR-145-5p could inhibit PLD5 resulting in downregulation of cell proliferation and metastasis in prostate cancer [ 36 ]. miR-1180-3p has been reported involving in the regulation of C11of54 in hepatocellular carcinoma and ST3GAL4 in cutaneous melanoma [ 30 , 37 ].…”
Section: Discussionmentioning
confidence: 99%